The Appilcation of Photogrammetry and Photo-interpretation in Indian Forestry - Ganguli, B. N. (Indian Forester, 1965)
The application of Aerial Photogrammetric techniques in forestry is now an approved practice in almost all the advanced countries of the world. In the fields of forest type mapping, forest and range management and wild life censuses, the available aerial photographs of the project area furnish quick and valuable information which with the more conventional methods will take a much longer time with additional expenditure. The author, during his stay in U.S,A., attended a course on "Aerial Photogrammetry and Photo-Interpretation in Forestry" at the University of Arizona. The course involved classroom lectures on basic principles as well as preparation of a forest-type map of the Santa Catalina mountains near Tucson, Arizona, U.S.A. The present article is based on the information collected in the c1assroom as well as in the field. It discusses the techniques of delineating and transferring details of a forest area from aerial photographs to a controlled base map and calculation of areas of individual types for timber volume determination and other forest valuation purposes. Lastly, a greater use of aerial photographs in Indian Forestry and a suitable training programme in Indian Forest College, Dehra Dun, has been suggested.